Hubungan Tingkat Stres pada Pandemi Covid-19 terhadap Kualitas Tidur Tenaga Kesehatan RSI Unisma - Tri Wahyu Sarwiyata; Pyarkatariana Putri E. P.; Mayvita Muntadiroh; Firsania Bunga W; Erfina Daniati; Erna Sulistyowati (Jurnal Kesehatan Islam : Islamic Health Journal, 2021)
Abstract. Introduction: The incidence of COVID-19 continued to increase due to human-to-human transmission. To prevent the transmission of COVID-19, the government applied self-quarantine regulation. However, health workers must continue to work, especially those located in big cities, such as Malang. One of the COVID-19 referral hospitals in Malang is the Rumah Sakit Islam Malang (RSI UNISMA). The high number of patients undergoing examination tests and handling COVID-19 treatment increased the workload of health workers at RSI UNISMA. Stress due to high workload had an impact on sleep quality disturbances. This study aimed to analyze the relationship between stress levels of health workers at RSI UNISMA on sleep quality during COVID-19.Methods: This type of research was an analytic observational study with a cross-sectional approach. The sampling technique used a simple random sampling method, with as many as 74 respondents. The questionnaire instrument was in the form of a google form regarding the Covid Perceived Stress Scale (COVID PSS-10 Items) which assesses stress levels and the Pittsburgh Sleep Quality Index (PSQI) which assesses sleep quality. Data analysis used SPSS 25.0 with fisher's exact test.Results: From a total of 74 respondents, there were 58 respondents who met the inclusion criteria. Based on statistical analysis, there was no relationship between stress levels and the sleep quality of UNISMA Hospital health workers during the COVID-19 pandemic (p > 0.05).Conclusion: There was no significant relationship between stress levels and the quality of sleep for health workers at RSI UNISMA during the COVID-19 pandemic. This can be caused by various factors, one of which is thought that the health worker is accustomed to doing work with a high level of stress or a deficiency in research methods such as classifying work units.